Morphology-based phylogeny of the suckermouth armored catfishes, with emphasis on the Neoplecostominae (Teleostei: Siluriformes: Loricariidae) - Pereira, Edson H. L.; Reis, Roberto E. (Zootaxa, 2017)
A phylogenetic study of the Loricariidae with emphasis on the Neoplecostominae is presented based on a maximum parsimony analysis of 268 phenotypic characters encompassing osteology, arthrology, and external morphology. Results support previous hypotheses of the monophyly of the Neoplecostominae and each of the included genera: Hirtella, Isbrueckerichthys, Kronichthys, Neoplecostomus, Pareiorhaphis, and Pareiorhina. In addition, previously undiscovered diversity was revealed within the subfamily as an additional genus-level taxon, herein described as Euryochus. Relationships among neoplecostomine genera are: (Kronichthys (Euryochus ((Hirtella + Pareiorhaphis) (Pareiorhina (Isbrueckerichthys + Neoplecostomus))))). Additional undescribed diversity was also detected among most neoplecostomine genera and the Hypoptopomatinae. In addition, recently discovered genera Nannoplecostomus and Microplecostomus were included in the analysis, and were identified as sequential sister-taxa to Neoplecostominae + Hypoptopomatinae, which are currently not included in any subfamily and regarded as incertae sedis in Loricariidae. The three species of Lithogenes were included in an encompassing phylogenetic analysis for the first time, and were identified as a monophyletic unit and sister group to all remaining loricariids. The other loricariid subfamilies were also corroborated as monophyletic, and presented the following interrelationships (Lithogeninae (Delturinae (Loricariinae (Hypostominae (Nannoplecostomus (Microplecostomus (Hypoptopomatinae + Neoplecostominae). The Neoplecostominae and its genera are phylogenetically diagnosed, and hypothesized relationships are compared to those of previous morphological and molecular phylogenetic studies.